Adaptif Teknologi Dalam Mendukung Penerapan Pembelajaran Digital Dan Literasi Numerasi Pada SMA Swasta Deli Murni Bandar Baru - Sanggam Pardede; Natalia Rajagukguk; Neksen Sihotang; Christina Verawaty Manalu; Enjelina putri Simbolon (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Community Service Program (PkM) for FKIP students at HKBP Nommensen University in Medan together with the team carried out Adaptive Technology activities to support the implementation of digital learning and numeracy literacy at Deli Murni Private High School. Technology adaptation refers to the process by which an identity, whether an individual, organization, or system, integrates and changes the way they operate or interact with new technology or innovation. Technology will affect the education system in Indonesia, one of which is schools with literacy and numeracy limitations. Numeracy literacy is the fundamental ability to understand, use and apply mathematical concepts in everyday situations. The method of implementing activities is carried out in the stages of survey, socialization, learning, evaluation and documentation. The results of activities carrying out administrative tasks at school using technology such as laptops and computers, completing various files through the school dapodik book, dividing teams, we carry out activities according to school needs including helping guidance and counseling teachers every morning before marching, the school administration center, working on documents and help teachers in doing assignments.